2017
DOI: 10.1002/smr.1918
|View full text |Cite
|
Sign up to set email alerts
|

Internal quality assurance for external contributions in GitHub: An empirical investigation

Abstract: For popular open‐source software projects, there are always a large number of worldwide developers who have been glued to making code contributions, while most of these developers play the role of casual contributors because of their very limited code commits. The frequent turnover of such a group of developers and the wide variations in their coding experiences challenge the project management on code and quality. This paper aims to investigate the status quo of internal quality assurance for external contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The quality theme also permeates a number of challenges (32% of all reported challenges). As the collective intelligence creates high-quality content, the wide variations among the crowd's knowledge levels challenge the quality management of the massive number of contributions [34]. Moreover, assessing the quality of content and knowledge is much more difficult than assessing the quality of code in the OSS context.…”
Section: ) Quality Assurancementioning
confidence: 99%
“…The quality theme also permeates a number of challenges (32% of all reported challenges). As the collective intelligence creates high-quality content, the wide variations among the crowd's knowledge levels challenge the quality management of the massive number of contributions [34]. Moreover, assessing the quality of content and knowledge is much more difficult than assessing the quality of code in the OSS context.…”
Section: ) Quality Assurancementioning
confidence: 99%
“…They proposed a defect classification scheme in order to enumerate the types of defects that can be identified by static tools, and concluded that automated code inspection faults can be used as efficient predictors of failures. Yao Lu et al investigated internal quality of the code made by casual Contributors in OSS projects within GitHub [2]. They proposed a method to estimate developers' code quality using the ''Code Quality Issue Density (CQID)'' metric and concluded that casual contributors tend to introduce a greater quantity of CQIs with greater severity than the main contributors and casual contributors tend to introduce CQIs on coding convention, errorhandling, CWE (Common Weekness Enumeration) and brain-overload, which can decline the readability, reliability, efficiency and testability of the software.…”
Section: Related Work a Static Analysis And Code Qualitymentioning
confidence: 99%
“…Generally, code quality can be classified as internal and external quality attributes [4]. The external quality attributes are reflected at runtime stage such as functionality and correctness, while internal quality attributes exist in development and maintenance [2], which is concerned by developers, such as maintainability and readability. High internal quality source code not only improves the readability of code and help developers quickly understand explicit and implicit meanings expressed by code, but also reduces the risk of crash and the cost of software maintenance [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations